Original Research by Young Twinkle Students (ORBYTS): ephemeris refinement of transiting exoplanets. Issue 4 (7th May 2020) - Edwards, Billy; Changeat, Quentin; Yip, Kai Hou; Tsiaras, Angelos; Taylor, Jake; Akhtar, Bilal; AlDaghir, Josef; Bhattarai, Pranup; Bhudia, Tushar; Chapagai, Aashish; Huang, Michael; Kabir, Danyaal; et al.
ABSTRACT: We report follow-up observations of transiting exoplanets that have either large uncertainties (>10 min) in their transit times or have not been observed for over 3 yr. A fully robotic ground-based telescope network, observations from citizen astronomers, and data from TESS have been used to study eight planets, refining their ephemerides and orbital data. Such follow-up observations are key for ensuring accurate transit times for upcoming ground- and space-based telescopes, which may seek to characterize the atmospheres of these planets. We find deviations from the expected transit time for all planets, with transits occurring outside the 1 σ uncertainties for seven planets. Using the newly acquired observations, we subsequently refine their periods and reduce the current predicted ephemeris uncertainties to 0.28–4.01 min. A significant portion of this work has been completed by students at two high schools in London as part of the Original Research By Young Twinkle Students (ORBYTS) programme.